Pensamento computacional: uma análise dos cursos de licenciatura em Matemática da Unesp - Silva, Rogério Aparecido Batista da (2023)
When aiming at identifying Computational Thinking elements present in PPP (PoliticalPedagogical Projects) and examining interviews with coordinators and teachers of these courses, the main emphasis falls on the question: How is Computational Thinking shown in Mathematics Degree Courses at Unesp? In order to achieve this goal, this research is based on the Constructionism concepts, which highlights the synergy among educational processes, learning methods and the use of computational resources. Through a qualitative approach, this investigation undertakes a meticulous analysis of documents, such as political-pedagogical projects and lesson plans for the subjects included in the Mathematics Degree Courses. Furthermore, it incorporates semi-structured interviews carried out via videoconference, conducted with coordinators and teachers who are part of this Course at six Unesp units. In our research, we did not find explicit Computational Thinking evidence in PPP. Based on this, we established connections between the pillars of Computational Thinking and the speeches of the interviewees, based on disciplines that focus on programming. The Computational Thinking pillars used for this research were: abstraction, analysis and automation. Data analysis revealed a strong tendency towards the automation pillar; nevertheless, as already mentioned, the PC is not explicitly shown at Unesp Mathematics Degree Courses. However, there are indications of its manifestation, driven by the use of digital technologies in the classroom. Through the use of these technologies, we identified the three pillars, with special attention to the subcategories "Machines" and "Feasibility", present in the automation and analysis pillars.